Mathematics in Good Will Hunting II: problems from the students perspective - Horváth, Gábor; Korándi, József; Szabó, Csaba (Teaching Mathematics and Computer Science, 2013)
This is the second part of a three paper long series exploring the role of mathematicians and of the mathematical content occurring in popular media. In particular we analyze the drama film Good Will Hunting. Here we investigate the mathematical content of the movie by considering the problems appearing in it. We examine how a mathematician or a mathematics student would solve these problems. Moreover, we review how these problems could be integrated into the higher education of Hungary.